If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/3)*(2*x+1) = 3*(1-(4*x))+10 // - 3*(1-(4*x))+10
(1/3)*(2*x+1)-(3*(1-(4*x)))-10 = 0
(1/3)*(2*x+1)-3*(1-4*x)-10 = 0
1/3*(2*x+1)-3*(1-4*x)-10 = 0
1/3*(2*x+1)-3*(1-4*x)-10 = 0
38/3*x-10-8/3 = 0
38/3*x-38/3 = 0
38/3*x-38/3 = 0
38/3*x-38/3 = 0 // + 38/3
38/3*x = 38/3 // : 38/3
x = 38/3/38/3
x = 1
x = 1
| 10-6n=-44 | | 5z+10=105 | | 5(2t-1)=3(t+3) | | 51=1+10m | | x/2-10=x/5+1/2 | | 7(3z-4)=5(2z+1) | | -b/15+10=11 | | x^2+y^2=20x | | 7(4y-5)=11(2y-1) | | -2-5x(-2)-3x(-4)= | | 21=-3+6r | | -3x-7=-40 | | 7+10x+38=9+14x | | r/6+9=8 | | 10x+10=701 | | 3x-7(0)=27 | | 78-5x=22x+15 | | -1x-8+2x+2=4x-12 | | 2x-4/3 | | 6x+1+2x-3=94 | | (-1331)^2/3 | | -15x+35(23)=-135 | | 2X[-10]-9Y=-38 | | 3x-7(23)=27 | | 4v^3x^4-6x^2/2x^3y^5 | | 2x^2+3-x=0 | | 8/5*6/7 | | 3/8*5/7 | | 60x+5(6-x)=10(-74) | | fsav=aved | | 2x+39=12x-1 | | 5-9x=57-37 |